Chemistry modelling skills: students’ understanding on transferring simple molecule to model drawing - Omar, S. Z. (American Scientific Publishers, 2017)
The purpose of this paper is to investigate students’ understanding on the third hierarchy of the chemistry modelling skills; transferring simple molecule to model drawing. A total of 112 form four Malaysian school students were participated in this study. The Chemistry Modelling Skills Test (CMST) was used as an instrument for data collection. The collected data was analyzed qualitatively. The findings showed that, the majority of the students exhibited a non-scientific understanding and a significant number exhibited a scientific understanding regarding the transfer of a simple molecule to model drawing. Only a minority of the students exhibited no understanding. This study also had identified six learning difficulties faced by students which were first, determining the angle between the atoms. Second, distinguish different types of atoms. Third, indicate the bond that exists between the atoms. Fourth, determine the number of atoms in subscripts. Fifth, differentiate between atoms and ions. Sixth, understanding the bonding rules in chemical bond. Based on the students’ difficulties, the used of learning approach that emphasized on visualization of structure of molecules are suggested.